Roles of Chlorogenic Acid on Regulating Glucose and Lipids Metabolism: A Review. (25th August 2013) - Meng, Shengxi; Cao, Jianmei; Feng, Qin; Peng, Jinghua; Hu, Yiyang
Abstract : Intracellular glucose and lipid metabolic homeostasis is vital for maintaining basic life activities of a cell or an organism. Glucose and lipid metabolic disorders are closely related with the occurrence and progression of diabetes, obesity, hepatic steatosis, cardiovascular disease, and cancer. Chlorogenic acid (CGA), one of the most abundant polyphenol compounds in the human diet, is a group of phenolic secondary metabolites produced by certain plant species and is an important component of coffee. Accumulating evidence has demonstrated that CGA exerts many biological properties, including antibacterial, antioxidant, and anticarcinogenic activities. Recently, the roles and applications of CGA, particularly in relation to glucose and lipid metabolism, have been highlighted. This review addresses current studies investigating the roles of CGA in glucose and lipid metabolism.